Description of three new species of Hylopanchax Poll & Lambert, 1965 from the central Congo Basin (Cyprinodontiformes: Poeciliidae: Procatopodini) with a redefinition of the genus - Zee, Jouke R. Van Der; Sonnenberg, Rainer; Schliewen, Ulrich K. (Zootaxa, 2013)
Three new species of the lampeye genus Hylopanchax are described from the central Congo basin: H. leki, new species, H. ndeko, new species, and H. moke, new species. These differ considerably in body shape from the two previously described species, H. stictopleuron and H. silvestris, with two deep bodied and one small and slender species. A redefinition of the diagnostic characters of the genus Hylopanchax is presented, including pronounced sexual dimorphism.